Peran Kepuasan Kerja Sebagai Intervening pada Hubungan Work-Life Balance dan Lingkungan Kerja Terhadap Loyalitas Karyawan di PT XYZ - Sarmin Sarmin; Soedjatmoko Soedjatmoko; Aji Wuryoko; Pika Dwi Marliana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the role of work–life balance and the work environment in shaping employee loyalty, with job satisfaction acting as a mediating variable, at PT XYZ operating in the aviation industry. A quantitative approach with an associative research design was employed. Data were collected through a structured questionnaire distributed to employees and subsequently analyzed using multiple linear regression and path analysis to assess both direct and indirect relationships among the variables. The analysis results show that WLB and the work environment have been proven to have a significant and positive influence on job satisfaction. Meanwhile, both variables also have a positive and significant impact on employee loyalty. The findings of the path analysis revealed that job satisfaction functions as an intervening variable in the relationship between WLB and employee loyalty, where the indirect effect through job satisfaction (0.356) is greater than the direct effect (0.264). A similar pattern was also found in the relationship between the work environment and employee loyalty, with an indirect effect of 0.284 exceeding the direct effect of 0.121. These results indicate that job satisfaction has a strategic role in strengthening employee loyalty.